2020
DOI: 10.36660/abc.20190271
|View full text |Cite
|
Sign up to set email alerts
|

Função Diastólica e Biomarcadores de Participantes de Caminhada de Longa Distância

Abstract: Fundamento: Os efeitos da caminhada de longa distância sobre o sistema cardiovascular são pouco estudados. Objetivos: O objetivo geral deste estudo foi verificar esses efeitos sobre o comportamento da função diastólica e dos biomarcadores cardíacos CK-MB (massa), troponina T e NT-proBNP em atletas amadores. Método: Este estudo longitudinal realizado em 2015 avaliou os participantes nas 5 etapas seguintes: A0 (basal) antes de iniciar o percurso, e as demais, A1, A2, A3 e A4 ao final de cada dia, totalizando 244… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In this context, cardiac markers play an important role in understanding the intensity of exercise. Some academic studies have shown that although there is an increase in cardiac damage markers such as cardiac troponin, CK-MB, and NT-pro-BNP after moderate walking and low and moderate exercise intensity, this increase is not significant [47][48][49]. However, biochemical levels such as NT-pro-BNP, troponin, and CK-MB have been found to be elevated in long-distance marathon runners [19,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, cardiac markers play an important role in understanding the intensity of exercise. Some academic studies have shown that although there is an increase in cardiac damage markers such as cardiac troponin, CK-MB, and NT-pro-BNP after moderate walking and low and moderate exercise intensity, this increase is not significant [47][48][49]. However, biochemical levels such as NT-pro-BNP, troponin, and CK-MB have been found to be elevated in long-distance marathon runners [19,50,51].…”
Section: Discussionmentioning
confidence: 99%